2005
DOI: 10.1371/journal.ppat.0010010
|View full text |Cite
|
Sign up to set email alerts
|

A Surface Groove Essential for Viral Bcl-2 Function During Chronic Infection In Vivo

Abstract: Antiapoptotic Bcl-2 family proteins inhibit apoptosis in cultured cells by binding BH3 domains of proapoptotic Bcl-2 family members via a hydrophobic BH3 binding groove on the protein surface. We investigated the physiological importance of the BH3 binding groove of an antiapoptotic Bcl-2 protein in mammals in vivo by analyzing a viral Bcl-2 family protein. We show that the γ-herpesvirus 68 (γHV68) Bcl-2 family protein (γHV68 v-Bcl-2), which is known to inhibit apoptosis in cultured cells, inhibits both apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 89 publications
(130 reference statements)
6
79
0
Order By: Relevance
“…Similar to cellular Bcl-2, we and others found that the vBcl-2 encoded by KSHV and γ-HV68 effectively attenuates autophagy through a direction interaction with Beclin1, surprisingly in a manner more potently than their cellular counterpart (66,67,69,70). Structural analyses further implicated that the two functions of vBcl-2, anti-apoptosis and anti-autophagy, engage the similar if not the same structural cassette, the hydrophobic BH3-binding groove on the surface of vBcl-2 (66,69). Yet, the affinity of vBcl-2 to Beclin1 is apparently higher than to pro-apoptotic molecules, suggesting that is recently found to induce autophagy to facilitate viral lytic replication, as blunting cellular autophagy reduces the virus's ability to reactivate from latency (78).…”
Section: β-Herpesvirussupporting
confidence: 53%
See 1 more Smart Citation
“…Similar to cellular Bcl-2, we and others found that the vBcl-2 encoded by KSHV and γ-HV68 effectively attenuates autophagy through a direction interaction with Beclin1, surprisingly in a manner more potently than their cellular counterpart (66,67,69,70). Structural analyses further implicated that the two functions of vBcl-2, anti-apoptosis and anti-autophagy, engage the similar if not the same structural cassette, the hydrophobic BH3-binding groove on the surface of vBcl-2 (66,69). Yet, the affinity of vBcl-2 to Beclin1 is apparently higher than to pro-apoptotic molecules, suggesting that is recently found to induce autophagy to facilitate viral lytic replication, as blunting cellular autophagy reduces the virus's ability to reactivate from latency (78).…”
Section: β-Herpesvirussupporting
confidence: 53%
“…Bad) activate it (67,68). Similar to cellular Bcl-2, we and others found that the vBcl-2 encoded by KSHV and γ-HV68 effectively attenuates autophagy through a direction interaction with Beclin1, surprisingly in a manner more potently than their cellular counterpart (66,67,69,70). Structural analyses further implicated that the two functions of vBcl-2, anti-apoptosis and anti-autophagy, engage the similar if not the same structural cassette, the hydrophobic BH3-binding groove on the surface of vBcl-2 (66,69).…”
Section: β-Herpesvirusmentioning
confidence: 55%
“…2A is the alignment of the BH1 sequences of Bcl-xL and BHRF1. Structural studies have suggested that the hydrophobic groove of BHRF1 is inaccessible; however, mutational analysis has indicated the region is important for its function (12,21,22). To test whether the BH1 region of BHRF1 is required for protection, BHRF1 was mutated at residues analogous to those responsible for hydrophilic interactions between Bcl-xL and Bim (1), specifically, L98, G99, and R100.…”
Section: Bhrf1 Protects Cells From Bim-dependent Apoptosis Via Its Bh3mentioning
confidence: 99%
“…Indeed, adenovirus is not the only virus family to encode a BAX and BAK antagonist. Poxviruses and herpesviruses have since been found to encode BAX and/or BAK BH3-interacting and inhibitory proteins [46][47][48][49][50][51][52] some of which are BCL-2 homologs, and some not. Still other viruses encode BCL-2 homologs whose mechanism of action has yet to be determined.…”
Section: Apoptosis Induced By Viral Infection Is Blocked Primarily Bymentioning
confidence: 99%